PENGARUH MOTIVASI, KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU EKONOMI SMA DI PALEMBANG - Hermansyah Hermansyah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
The experiment was conducted at 122 public and private schools in Palembang, totally consisting of 267 teachers classified according to the school accreditation, namely; A, B, and C. The measuring of teachers’ performance concept used here refers to the opinion introduced by Moorhead, namely; dimensions of quality, quantity, cooperation, innovation, and self-standing. The test-result on regression showed that partially, motivation, commitment, and competence affect the teachers’ performance with a correlation coefficient of 0.701. Simultaneously, motivation variable, commitment, and competence have an influence on the teachers’ performance with a correlation coefficient of 0,911. Variables of commitment and competence are very much correlated to the teachers’ performance with a coefficient of 0.818 and 0.810. The very dominant influencing contribution of free variables is commitment. This is shown by the contribution of commitment variable of 66.91%, meaning that the commitment variable plays its role very dominantly compared with other free variables.